Untersuchungen zum Einsatz hochauflösender bathymetrischer LIDAR Daten in der2D-Abflusssimulation und Habitatmodellierung - Jocham, Stefan (Forum Umwelttechnik und Wasserbau, 2022)
In the present thesis, the use of high-resolution bathymetric survey data from Airborne LIDAR Bathymetry (ALB) in hydrodynamic-numerical (HN) modelling and physically based habitat modelling is investigated. Two near-natural river reaches at the river Lech in Bavaria and the river Ahr in South Tyrol were exemplary used therefore.